IDENTIFIKASI PANGAN LOKAL PADA 2 PASAR LOKAL KOTA WAIKABUBAK, SUMBA BARAT, PROV. NUSA TENGGARA TIMUR - Takaeb, Matheos (Fakultas Sains dan Teknologi, Universitas Nasional Karangturi, 2025)
Local food has an important role in maintaining food security in a region. Each region has a unique type of food that not only meets the consumption needs of the community, but also becomes part of local wisdom that has been passed down from generation to generation. Thus, the study of local food is very important to understand how this potential can be maximized. Therefore, this research is important to be conducted to identify the role, potential, and sustainable local food development strategy, so that it can be a solution in maintaining food security, improving community nutrition, and strengthening the local economy. Data collection was carried out using a survey method in 2 local markets (New Market and Old Market) in Waikabubak City, Dira Tana District, West Sumba Regency, Prov. NTT. The data that will be collected in this activity consists of primary data (type of food). The determination of the sample was carried out by purposive sampling technique. After mapping food products in 2 local markets in Waikabubak city, data was successfully collected in the form of 69 types of local food plants available in the new Waikabubak market and 62 types of local food available in the old market. It is also known that the food available in these 2 local markets has been cultivated by the community on their own land (gardens) and rice fields.